Pengaruh Citra Merek dan Word Of Mounth (WOM) Terhadap Loyalitas Pelanggan dengan Kepuasan Sebagai Mediasi - Biyan Aditia Ramadhan; Endang Tjahjaningsih (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study examines the effect of brand image and word of mouth on customer loyalty, with customer satisfaction as a mediating variable at Rizka Hijab Tasikmalaya. The research aims to provide practical insights for management in designing marketing strategies that enhance customer satisfaction and long-term loyalty. A quantitative explanatory approach was employed. The population consisted of all customers of Rizka Hijab Tasikmalaya, with 107 respondents selected using non-probability sampling. Data were collected through questionnaires that had passed validity and reliability testing. The analysis used multiple regression and the Sobel test to evaluate both direct and indirect effects among variables. The findings show that brand image has a positive and significant effect on customer satisfaction, while word of mouth does not significantly influence satisfaction. Brand image does not directly affect customer loyalty, whereas word of mouth and customer satisfaction both have positive and significant effects on loyalty. Furthermore, customer satisfaction mediates the relationship between brand image and loyalty but does not mediate the relationship between word of mouth and loyalty. These results highlight the strategic importance of strengthening brand image and maintaining customer satisfaction to build sustainable customer loyalty.